2006
DOI: 10.1017/s0959269506002535
|View full text |Cite
|
Sign up to set email alerts
|

When perception isn't reality: Accent identification and perceptual dialectology in French

Abstract: ab st rac tThis article examines levelling and diversity in northern urban French pronunciation through the optic of folk (= non-linguists') perceptions of variation. These perceptions are investigated by the identification of authentic voice samples (rather than other instruments widely used in perceptual dialectology such as mental mapping): respondents from the Pays de la Loire region of north-western France heard extracts of scripted speech from Nancy and Rennes, and were asked to identify the speakers' re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 18 publications
2
17
0
10
Order By: Relevance
“…It was discovered that whilst listeners were generally able to make distinctions between Northern and Southern forms of US English -they had greater difficulty distinguishing between Northern and Midland US English -which suggests, with regards to linguistic diversity in US English, the north-south distinction is especially salient for the general public in the United States (see also McKenzie & Osthus, 2011). Further research focussing specifically upon listeners' ability to identify and categorise the place of origin of native speakers of the language under consideration has since been undertaken in a range of countries including: Wales (Williams, Garrett & Coupland, 1999); The Netherlands (Van Bezooijen & Gooskens, 1999); France (Boughton, 2006); Denmark (Ladegaard, 2001); Japan (Morris, 2010); and continues apace in the United States (Purnell, Idsardi & Baugh, 1999;Thomas, Lass & Carpenter, 2010). Taken together, the results of these studies reveal that native speaker participants, asked to listen to speech stimulus, are generally able to accurately and consistently identify speakers' places of origin and/or varieties of a given language as regionally or socially localised forms, provided the regional identity of each individual speaker is not too fine-grained for the hearer.…”
Section: One Of the Earliest Studies Conducted Amongst Native Englismentioning
confidence: 99%
“…It was discovered that whilst listeners were generally able to make distinctions between Northern and Southern forms of US English -they had greater difficulty distinguishing between Northern and Midland US English -which suggests, with regards to linguistic diversity in US English, the north-south distinction is especially salient for the general public in the United States (see also McKenzie & Osthus, 2011). Further research focussing specifically upon listeners' ability to identify and categorise the place of origin of native speakers of the language under consideration has since been undertaken in a range of countries including: Wales (Williams, Garrett & Coupland, 1999); The Netherlands (Van Bezooijen & Gooskens, 1999); France (Boughton, 2006); Denmark (Ladegaard, 2001); Japan (Morris, 2010); and continues apace in the United States (Purnell, Idsardi & Baugh, 1999;Thomas, Lass & Carpenter, 2010). Taken together, the results of these studies reveal that native speaker participants, asked to listen to speech stimulus, are generally able to accurately and consistently identify speakers' places of origin and/or varieties of a given language as regionally or socially localised forms, provided the regional identity of each individual speaker is not too fine-grained for the hearer.…”
Section: One Of the Earliest Studies Conducted Amongst Native Englismentioning
confidence: 99%
“…Participants are often asked to respond to dialectal variation by judging varieties and their speakers along a variety of semantic-differential scales (e.g., Ladegaard, 1998;McKenzie, 2008;Plewnia & Rothe, 2009). For example, Boughton (2006), in a study investigating northern urban French pronunciation, found that the respondents from a variety of regions and social backgrounds made judgements about dialect speakers based on social stereotypes. Listeners in that study assumed that speakers who used nonstandard pronunciation were of rural origin or of a lower social class.…”
Section: Introductionmentioning
confidence: 99%
“…2 For example, some studies test listeners' abilities to accurately identify speaker ethnicity based on the presence of particular linguistic variables (Graff et al, 1986;Thomas and Reaser, 2004;Torbert, 2004Torbert, , 2010. Others look at identifying regional dialect or foreign accents (Boughton, 2006;Clopper and Pisoni, 2004;Fridland et al, 2004;Torbert, 2004Torbert, , 2010MacLeod, 2012;van Bezooijen and Gooskens, 1999;Williams et al, 1999). The following section provides examples of studies that have used the experimental approach to defining salience.…”
Section: The Experimental Approach To Saliencementioning
confidence: 99%